How do you solve #12- 3q - 9q = - 12#?

1 Answer

Answer:

#q = 2#

Explanation:

The great thing about equations is that we can do (almost) any operation on both sides while maintaining its equality.

We can simplify

#12 - 3q - 9q = -12#

as

#12 - 12q = -12#

by grouping together the terms with q in it.

Now we can add #12q# to both sides of the equation and the equation will still be true. So:

#12 - 12q + 12q = -12 + 12q#

That is

#12 = -12 + 12q#

Now add #12# to both sides of the equation. So:

#12 + 12 = -12 + 12 + 12q#

That is

# 24 = 12q#

Now let's divide both the sides of the equation by #12#. So:

#24/12 = (12q)/12#

That is

#2 = q#

Hence we have obtained the value of #q# that solves the given equation, #q = 2#.

Have a wonderful day!!!